Perbandingan Metode Tafsir Ulama Asia Tenggara dan Timur Tengah dalam Isu Sosial Politik, Feminisme, dan Ekologi - Amin, Abdul; Jabbar, Luqman Abdul (Jurnal Teologi Islam, 2026)
The development of Qur'anic interpretation in the contemporary era shows a tendency to be increasingly responsive to current issues such as socio-political issues, feminism, and the ecological crisis. This article aims to analyze and compare the exegetical methodologies developed by Southeast Asian and Middle Eastern scholars over the past five years. Using a library study approach in reputable scientific journals, this study finds that Southeast Asian scholars tend to prioritize sociological contextual interpretations rooted in local realities, while Middle Eastern scholars emphasize the maqāṣid al sharī‘ah approach and critical hermeneutics. These differences demonstrate the epistemological diversity of contemporary exegesis and open up space for methodological dialogue between regions.